The functional dynamics of FicD’s TPR domain are modulated by the interaction with ATP and BiP - Svenja Runge; Ecenaz Bilgen; Andrea Magni; Giorgio Bonollo; Giorgio Colombo; Aymelt Itzen; Don C. Lamb (Proceedings of the National Academy of Sciences, 2025)
The human Fic enzyme FicD plays an important role in regulating the Hsp70 homolog BiP in the endoplasmic reticulum: FicD reversibly modulates BiP’s activity through attaching an adenosine monophosphate to the substrate binding domain. This reduces BiP’s chaperone activity by shifting it into a conformation with reduced substrate affinity. Crystal structures of FicD in the apo, adenosine triphosphate (ATP)-bound, and BiP-bound states suggested significant conformational variability in the tetratricopeptide repeat (TPR) motifs. However, nothing is known about the underlying dynamics. In this study, we investigate the conformational dynamics of FicD’s TPR motifs using two-color, single-molecule Förster resonance energy transfer (smFRET) experiments. We demonstrate that the TPR motifs exhibit conformational dynamics between a TPR-out and a TPR-in conformation on timescales ranging from microseconds to milliseconds. In addition, we extend our investigation on multiple labeling positions within FicD, revealing how conformational dynamics vary depending on the location within the TPR motif. We quantify the motions with dynamic photon distribution analysis for the FRET constructs and generate an ensemble of structures for the different states consistent with the smFRET data using molecular dynamic simulations. We propose a conformational landscape model for FicD where the TPR-in/out states exist in equilibrium and the fraction of dynamic population is altered due to the presence of ATP and BiP. These results indicate that not only is FicD dynamic, but the dynamics are linked to the functionality and interactions of FicD with BiP.